ENVIRONMENT HEALTH KNOWLEDGE OF STUDENT AT UNIVERSITY FROM DIFFERENT COUNTRIES - Fabrice Paulin Ketchagmen Fosso, Fidan Aslanova (Chelonian Research Foundation, 2024)
The research focuses on assessing international students' understanding of environmental health in order to improve their knowledge, cognition and perceptions on environmental health issues. we use a mixed methods approach, collecting data through questionnaires and structured discussions. Participants from diverse nations and communities are selected using a diverse sampling technique to ensure inclusiveness. The study aims to identify potential knowledge gaps and growth opportunities, thereby enriching sustainability education among students. Ultimately, the research aims to raise awareness and educate students on environmental issues in order to create a cleaner, healthier future. Empowered students can be key agents of change in environmental conservation efforts. By fostering environmental literacy, students gain a stronger voice in environmental discussions. The survey assesses participants' skills, understanding, and perspectives on the natural world. He highlights the importance of internet communication and medical awareness in discussions about environmental health. A questionnaire including sections on socioeconomic background, environmental and health information, risk perceptions, health-related attitudes and behaviors was used in a longitudinal study involving students from diverse backgrounds. Keywords: learners, health in the community, risk awareness, and opinions about hazards posed by the environment.